2012
DOI: 10.2147/ijn.s35510
|View full text |Cite
|
Sign up to set email alerts
|

Application of magnetically induced hyperthermia in the model protozoan Crithidia fasciculata as a potential therapy against parasitic infections

Abstract: Background: Magnetic hyperthermia is currently a clinical therapy approved in the European Union for treatment of tumor cells, and uses magnetic nanoparticles (MNPs) under time-varying magnetic fields (TVMFs). The same basic principle seems promising against trypanosomatids causing Chagas disease and sleeping sickness, given that the therapeutic drugs available have severe side effects and that there are drug-resistant strains. However, no applications of this strategy against protozoan-induced diseases have b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…We would like to note that although the observed temperature increase Δ T ≈ 3.5 °C might seem insufficient for inducing a therapeutic effect, this temperature change represented an average bulk effect and not the temperature of the particle surface. Indeed, several recent studies demonstrated large local temperature gradients in the proximity of particles, which can surpass the average heating by more than an order of magnitude. Furthermore, local heating effects have been demonstrated to negatively affect the cell viability even in cases when the bulk temperature was not seen to measurably increase. …”
Section: Resultsmentioning
confidence: 99%
“…We would like to note that although the observed temperature increase Δ T ≈ 3.5 °C might seem insufficient for inducing a therapeutic effect, this temperature change represented an average bulk effect and not the temperature of the particle surface. Indeed, several recent studies demonstrated large local temperature gradients in the proximity of particles, which can surpass the average heating by more than an order of magnitude. Furthermore, local heating effects have been demonstrated to negatively affect the cell viability even in cases when the bulk temperature was not seen to measurably increase. …”
Section: Resultsmentioning
confidence: 99%
“…It has also shown promise when treating a cutaneous infection of Staphylococcus aureus , a major pathogen that often infects soft tissue wounds 17 . Magnetic hyperthermia has also been shown to kill Crithidia fasciculata , a non-pathogenic protozoan species 18 , but to our knowledge, no report of the use of this technology against human-infective protozoan species such as Leishmania spp has been shown. Harnessing heat generated by magnetic hyperthermia to target pathogens is therefore an attractive, non-chemotherapeutic and novel alternative approach to treating CL that could offer a convenient, cost effective solution to the issues associated with conventional thermotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, it was recently appreciated in several in-vitro experiments using low concentration of MNPs in cell culture dishes that there is no need of global increase in the cell temperature to induce tumor cell death. [7][8][9][10][11][12][13] Different hypotheses have been proposed to explain cancer cell death in MH. One of them is based on recent experimental results showing that the temperature rises in the immediate vicinity of the MNPs.…”
mentioning
confidence: 99%